Switchable Polymerization Triggered by Fast and Quantitative Insertion of Carbon Monoxide into Cobalt–Oxygen Bonds. Issue 15 (18th February 2020) - Wang, Yong; Zhao, Yajun; Zhu, Shuaishuai; Zhou, Xingping; Xu, Jing; Xie, Xiaolin; Poli, Rinaldo
Abstract: A strategy that uses carbon monoxide (CO) as a molecular trigger to switch the polymerization mechanism of a cobalt Salen complex [salen=( R, R )‐ N, N′ ‐bis(3, 5‐di‐ tert ‐butylsalicylidene)‐1, 2‐cyclohexanediamine] from ring‐opening copolymerization (ROCOP) of epoxides/anhydrides to organometallic mediated controlled radical polymerization (OMRP) of acrylates is described. The key phenomenon is a rapid and quantitative insertion of CO into the Co−O bond, allowing for in situ transformation of the ROCOP active species (Salen)Co III ‐OR into the OMRP photoinitiator (Salen)Co III ‐CO2 R. The proposed mechanism, which involves CO coordination to (Salen)Co III ‐OR and subsequent intramolecular rearrangement via migratory insertion has been rationalized by DFT calculations. Regulated by both CO and visible light, on‐demand sequence control can be achieved for the one‐pot synthesis of polyester‐ b ‐polyacrylate diblock copolymers ( Đ <1.15). Abstract : Carbon monoxide is used as a molecular trigger to switch the polymerization mechanism of a cobalt Salen complex from ring‐opening copolymerization (ROCOP) of epoxides/anhydrides to organometallic mediated controlled radical polymerization (OMRP) of acrylates. Regulated by both CO and visible light, on‐demand sequence control can be achieved for the synthesis of polyester‐ b ‐polyacrylate diblock copolymers.